Associative properties of rapeseed napin and pectin: Competition between liquid-liquid and liquid-solid phase separation. (July 2019) - Amine, Chloé; Boire, Adeline; Kermarrec, Alice; Renard, Denis
Abstract: We investigated the assembly of a plant protein, rapeseed napin (NAP), mixed with a plant polysaccharide, highly methylated pectin (PEC). The optimum pH for NAP/PEC interactions was found at pH 4.0 for which the charge difference between the two biopolymers is the highest. Two types of phase transition were observed depending on pH and mixing ratios: liquid-solid and liquid-liquid phase separation. We showed that liquid-solid transition was favored by strong electrostatic attraction whereas liquid-liquid phase separation was promoted by weaker attraction. In addition, we highlighted a solid-to-liquid phase transition overtime for ratios with excess of proteins. We showed that polysaccharide charge neutralisation was a requisite for the transition as no rearrangement was observed when residual charges remained. The underlying mechanism leading to this transition remains to be explored. To the best of our knowledge, such solid-to-liquid transition has never been reported for protein-polysaccharide mixtures. Graphical abstract: Image 1 Highlights: Napin (NAP)/Pectin (PEC) electrostatic assembly was investigated at pH values between 4 and 7. Optimum pH for NAP/PEC interactions was found at pH 4. Liquid-solid phase transition was favored by strong electrostatic attraction. Liquid-liquid phase separation was promoted by weaker attraction. A solid-to-liquid phase transition was highlighted overtime for ratios with excess of proteins.